A review of size-dependent continuum mechanics models for micro- and nano-structures. (January 2022) - Roudbari, Mir Abbas; Jorshari, Tahereh Doroudgar; Lü, Chaofeng; Ansari, Reza; Kouzani, Abbas Z.; Amabili, Marco
Abstract: Recently, the mechanical behavior of micro-/nano-structures has sparked an ongoing debate, which leads to a fundamental question: what steps can be taken to investigate the mechanical characteristics of these structures, and characterize their performance? From the standpoint of the non-classical behavior of materials, size-dependent theories of micro-/nano-structures can be considered to analyze their mechanical behavior. The application of classical theories in the investigation of small-scale structures can lead to inaccurate results. Many studies have been published in the past few years, in which continuum mechanics models have been used to investigate micro-/nano-structures with different geometry such as rods, tubes, beams, plates, and shells. The mechanical behavior of these systems under different loading – resulting in vibration, wave propagation, bending, and buckling phenomena – is the focus of the review covered in this work. The present objective is to provide a detailed survey of the most significant literature on continuum mechanics models of micro-/nano-structures, and thus orient researchers in their future studies in this field of research. Highlights: Size-dependent continuum mechanics models for micro/nano-structures are reviewed. Vibration, wave propagation, and buckling/post-buckling analysis are thoroughly discussed. Classification of the problems in linear and nonlinear models. Providing a detailed survey to help researchers in their future studies in this field.